The Right to Disconnect: Rest in the Digital Age of Work from the International, European and Polish Law Perspectives - Kurzynoga, Małgorzata (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The aim of this article is to justify the thesis that the right to be offline (the right to disconnect from digital tools) is not a redundant term. It is an original and autonomous right, distinct from the general right to rest. It is a right that arises in the new world of work, shaped by constant electronic and digital connectivity, designed with other needs in mind and exemplifying the increased legal protection required for rest and family time in the modern digital age.